The Arabic manuscript tradition : a glossary of technical terms and bibliography--supplement - Gacek, Adam. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2008)
The present work supplements the original volume of The Arabic Manuscript Tradition (AMT), both its glossary of technical terms and bibliography. It includes new entries of technical terms, additional definitions of, and/or citations for, the entries already found in AMT, and recent publications on various aspects of Arabic manuscript studies arranged by subject. Among additional features there are illustrations of various Arabic letterforms and an alphabetical index of all works cited in both AMT and its supplement.